The Use of AAV Vector-based Gene Therapy in the Treatment of Ophthalmic Diseases. Literature Review - Z. A. Batyrova; A. Sh. Murtazalieva; J. M. Ramazanova; A. S.‑U. Batchaev (Oftalʹmologiâ)
Introduction. This review article is devoted to the study of the current state of gene therapy using adeno-associated viruses (AAV) in the treatment of ophthalmic diseases.Objective: The purpose: to evaluate the effectiveness and safety of using gene therapy in the treatment of hereditary and acquired eye diseases, as well as to discuss the latest achievements in this field. Materials and methods. A systematic review of scientific literature from the databases MEDLINE, PubMed, Cyberleninka, Mendeley, Web of Science and EMBASE was conducted. Key terms and their combinations were used for the search: “gene therapy”, “adeno-associated virus”, “ophthalmology”, “hereditary eye diseases”, “age-related macular degeneration”, “glaucoma”, “clinical trials”. The review includes clinical studies, expert articles, and meta-analyses focusing on the use of AAV in the treatment of ocular pathologies.Results. Research shows that gene therapy using AAV represents a promising direction in the treatment of eye diseases due to the immune isolation of the eye and the effectiveness of vector systems. However, AAV-induced immune responses remain a challenge and require the development of specific strategies to suppress them. The importance of developing less immunogenic capsids and new vector delivery methods to improve the safety and effectiveness of therapy is emphasized.Conclusion. Gene therapy using AAV opens up new possibilities for the treatment of hereditary and acquired eye diseases. Despite the existing problems associated with immune responses, modern advances in the development of vectors and methods of delivering genetic material portend high prospects for safer and more effective therapeutic approaches.